Generalized cubic relations in Hv -LA-semigroups. (3rd April 2018) - Ma, Xue-Ling; Zhan, Jianming; Khan, Madad; Gulistan, Muhammad; Yaqoob, Naveed
Abstract: The main purpose of this paper is to explore the structural properties of H v -LA-semigroups with respect to generalized cubic relations. Some generalized cubic equivalence relations in H v -LA-semigroups are investigated. Furthermore, certain results on generalized cubic relations by using the images and pre-images of H v -LA-semigroups are provided.